The Effect of Auditory and Visual Recommendations on Choice. (January 2023) - Mariadassou, Shwetha; Bechler, Christopher J.; Levav, Jonathan
We explore the effect of recommendation modality on recommendation adherence. Results from five experiments run on various online platforms ( N = 6, 103 adults from TurkPrime and Prolific) show that people are more likely to adhere to recommendations that they hear (auditory) than recommendations that they read (visual). This effect persists regardless of whether the auditory recommendation is spoken by a human voice or an automated voice and holds for hypothetical and consequential choices. We show that the effect is in part driven by the relative need for closure—manifested in a sense of urgency—that is evoked by the ephemerality of auditory messages. This work suggests that differences in the physical properties of auditory and visual modalities can lead to meaningful psychological and behavioral consequences.